1994
DOI: 10.1111/j.1476-5381.1994.tb17120.x
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of the antiarrhythmic effects of ischaemic preconditioning by blockade of bradykinin B2 receptors

Abstract: 1 The possibility that bradykinin is involved in the pronounced antiarrhythmic effects of ischaemic preconditioning in anaesthetized mongrel dogs was examined with the use of the selective B2 antagonist, icatibant . 2 Preconditioning, achieved by two 5 min occlusions of the left anterior descending coronary artery, followed 20 min later by a 25 min occlusion of the same artery resulted, during this prolonged occlusion, in less severe arrhythmias (VF 0% versus 47% in control non-preconditioned dogs), reductions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
41
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(44 citation statements)
references
References 26 publications
3
41
0
Order By: Relevance
“…The urinary and plasma BK-forming components are comprised of proteins that mediate their effects on vasculature by releasing BK [30][31][32][33]. It is also known that the tissue kallikrein present in the urine is originating from the kidney and it reflects the renal activity of BK [9]. Higher concentrations of prekallikrein levels may suggest the onset of renal abnormalities.…”
Section: The Bradykinin System and Diabetesmentioning
confidence: 99%
See 2 more Smart Citations
“…The urinary and plasma BK-forming components are comprised of proteins that mediate their effects on vasculature by releasing BK [30][31][32][33]. It is also known that the tissue kallikrein present in the urine is originating from the kidney and it reflects the renal activity of BK [9]. Higher concentrations of prekallikrein levels may suggest the onset of renal abnormalities.…”
Section: The Bradykinin System and Diabetesmentioning
confidence: 99%
“…It seems that the kinins may be generated in parallel with the formation of thrombin at inflammatory sites, since inactive plasma kallikrein can be activated by coagulant Hageman factor. The tissue kallikrein multigene family comprises a closely related cluster of genes that vary in number between the different mammalian species: 24 genes have been identified in the mouse, 20 in the rat, 3 in humans and 3 in the hamster [9].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the blockade of A1 receptors abolished, whereas the administration of A1 agonist mimicked the cardioprotective effects of PC Thornton et al, 1992). Parallel with this adenosine hypothesis, our research group proposed that bradykinin (BK), formed rapidly after the onset of ischaemia, plays also an important trigger role in the antiarrhythmic effect of PC (Végh et al, 1991b(Végh et al, , 19931994b). The administration of BK (Végh et al, 1991b) and the combined ACE/NEP inhibitor Z13752A, which increases endogenous BK levels by inhibiting the degradation of BK mimicked, whereas the blockade of BK2 receptors with icatibant markedly attenuated the antiarrhythmic effect of PC (Végh et al, 1994b).…”
Section: Initiation Of Ischaemic Preconditioning: Characteristics Andmentioning
confidence: 51%
“…It was shown that bradykinin, which is rapidly formed in the blood during hypoxia [21][22][23] plays an important trigger role in the preconditioning-induced protection, since it acting on the endothelial bradykinin B 2 receptors triggers the generation and release of other mediators, such as prostacyclin [14] and nitric oxide [24]. These diffusible mediators reaching the myocytes activate mechanisms, which are ultimately lead to the protection [25].…”
Section: Sudden Cardiac Death and Preconditioningmentioning
confidence: 99%